Social Motivations of Semantic Change: The Case of the Oxford Word of the Year - Gao, Kyra (Journal of Theory and Practice in Linguistics, 2024)
Semantic change, a common phenomenon in all languages, has always been a popular issue among linguists. Among them, “Old Words for New Meanings” is the most closely connected way with the change and development of human society. The word of the year is a summary of the significant social events of the year, reflecting the social ideology, but fewer studies have focused on “Old Words for New Meanings” before. Therefore, this paper provides a detailed and systemic analysis of semantic change in the Word and Shortlist of the Year published by the Oxford Dictionary from 2015–2019 on the basis of conceptual blending theory (CBT) from the perspective of sociocognitive linguistics. The case analysis revealed that approximately 1/3 of the hot words from 2015–2019 were “Old Words for New Meanings”. There are five ways to change the meaning of an old word: (1) scope change (broadening/narrowing), (2) status change (amelioration/pejoration), (3) semantic change (figurative meaning), and (4) class shift. The social motivations influencing words’ semantic change are as follows: (1) political factors; (2) facial factors; (3) environmental protection; and (4) technological development.